ANALISIS PENYIMPANAN OBAT DI INSTALASI FARMASI dr. RSUD RASIDIN PADANG - Leonard, Devid; Novita, Dian; Srimayarti, Berly Nisa; Fitri, Aznila (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Pharmaceutical logistics management is a critical aspect of healthcare service management in hospitals, including RSUD dr. Rasidin Padang. This study aims to explore pharmaceutical logistics management, focusing on human resources (HR), infrastructure, and drug storage procedures. A qualitative phenomenological approach was used, involving four key informants: the head of the pharmacy department, the pharmacy warehouse coordinator, and two drug and medical consumable logistics officers. The findings reveal that the existing HR is insufficient, particularly during periods of increased workload. Although the qualifications of the staff meet the requirements, no formal training on drug storage has been conducted. The infrastructure, such as warehouse space and storage equipment, is generally adequate but lacks essential items like ladders for accessing high shelves. Standard operating procedures (SOPs) are available and provide crucial guidance, but their implementation is hindered by workforce limitations. In conclusion, the pharmaceutical logistics management at RSUD dr. Rasidin Padang has a solid foundation but requires additional workforce, specialized training, and facility improvements to enhance effectiveness.Keywords: Pharmaceutical logistics, drug storage